Intelligent compassion : feminist critical methodology in the Women's International League for Peace and Freedom - Confortini, Catia Cecilia (Oxford studies in gender and international relations., 2012)
This book traces changes in ideas and policies of the Women's International League for Peace and Freedom (WILPF - the longest-living international women's peace organization) from 1945 to 1975. Focusing on three areas of the organization's work (disarmament, decolonization, and the conflict in Israel/Palestine), the book addresses the agent-structure problem in international relations, specifically asking to what extent activists can transcend the practices of their era given that they are also shaped by them.